Oesophageal sensation assessed by electrical stimuli and brain evoked potentials--a new model for visceral nociception. Issue 5 (November 1995) - Frøbert, O; Arendt-Nielsen, L; Bak, P; Funch-Jensen, P; Bagger, J P
Abstract : Sensory thresholds and brain evoked potentials were determined in 12 healthy volunteers using electrical stimulation of the oesophagus 28 and 38 cm from the nares. The peaks of the evoked potentials were designated N for negative deflections and P for positive. Continuous electrical stimulation (40 Hz) at the 38 cm position resembled heartburn (five of 12 subjects) while non-specific ('electrical') sensations were provoked at 28 cm (10 of 12). Thresholds of sensation and of pain were lower at the initial than the second determination, but did not differ with respect to stimulation site. The pain summation threshold to repeated stimuli (2 Hz, 5 stimuli) was determined for the first time in a viscus. This threshold was lower than the pain threshold to single stimuli at 38 cm (p < 0.02). Evoked potential latencies did not change significantly over a six month period while the N1/P2 amplitude was higher at the first measurement (p < 0.05). P1 and N1 latencies were significantly shorter 38 cm (medians 100 and 141 ms) than 28 cm from the nares (102 and 148 ms) (p = 0.04 and p = 0.008). Electrical stimulation of the oesophagus may serve as a human experimental model for visceral pain. Longer evoked potential latencies from the proximal compared with distal stimulations provide new information about the sensory pathways of the oesophagus.